2007
DOI: 10.1534/genetics.107.073007
|View full text |Cite
|
Sign up to set email alerts
|

Shs1 Plays Separable Roles in Septin Organization and Cytokinesis in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, five septins (Cdc3, Cdc10, Cdc11, Cdc12, and Shs1/Sep7) form the septin ring at the bud neck during vegetative growth. We show here that disruption of SHS1 caused cold-sensitive growth in the W303 background, with cells arrested in chains, indicative of a cytokinesis defect. Surprisingly, the other four septins appeared to form an apparently normal septin ring in shs1D cells grown under the restrictive condition. We found that Myo1 and Iqg1, two components of the actomyosin contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
1
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 64 publications
6
67
1
9
Order By: Relevance
“…On galactose medium and at 25°, cells lacking Cdc10 are able to survive , but, we found that, under the same conditions, such cells were not viable if they also lacked Shs1 ( Figure 1C, top middle), confirming an observation made by Iwase et al (2007). Either Shs1 or Shs1-eGFP was able to restore viability ( Figure S1B).…”
Section: Shs1 Is Essential For Viability In Four Different Genetic Basupporting
confidence: 75%
See 3 more Smart Citations
“…On galactose medium and at 25°, cells lacking Cdc10 are able to survive , but, we found that, under the same conditions, such cells were not viable if they also lacked Shs1 ( Figure 1C, top middle), confirming an observation made by Iwase et al (2007). Either Shs1 or Shs1-eGFP was able to restore viability ( Figure S1B).…”
Section: Shs1 Is Essential For Viability In Four Different Genetic Basupporting
confidence: 75%
“…By contrast, absence of the fifth, mitotically expressed septin gene SHS1, a close paralog of CDC11 (Pan et al 2007), causes rather minor and subtle phenotypes (Iwase et al 2007;Egelhofer et al 2008;Garcia et al 2011;Buttery et al 2012). We explored whether compromising the function of another septin might provide a sensitized genetic background wherein presence of Shs1 becomes essential for viability.…”
Section: Shs1 Is Essential For Viability In Four Different Genetic Bamentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively timely expression during the cell cycle might be compromised (Beilharz and Preiss 2007). The process of septin assembly is sensitive to protein levels, for example overexpression of the septins compromises cell morphology and septin organization (Sopko et al 2006;Iwase et al 2007) and therefore higher levels of septins and/or septin assembly factors could lead to septin organization defects.…”
Section: Resultsmentioning
confidence: 99%